(untitled) (Innovative professional education, 2024)
Тhe publication summarizes the scientific achievements of fundamental research on counseling students of professional (vocational and technical) education in youth entrepreneurship. The essence of the coaching approach as an effective basis for preparing students of vocational education for entrepreneurship is substantiated. Coaching strategies for advising students of professional education in youth entrepreneurship are characterized based on the understanding of entrepreneurship as a real opportunity to contribute to the development of society and the awareness of an entrepreneur as an energetic and proactive person, a generator of interesting ideas, capable of qualitatively organizing the implementation of these ideas and achieving success in the initiated case